2004
DOI: 10.1002/ptr.1448
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of bone loss by oil extract of garlic (Allium sativum Linn.) in an ovariectomized rat model of osteoporosis

Abstract: The effects of oil extract of garlic (Allium sativum Linn.) on different primary and secondary osteoporotic marker changes were tested in an ovariectomized rat model of osteoporosis. Experiments were performed on three different rat models: sham-operated control, ovariectomized and ovariectomized supplemented with garlic oil. In ovariectomized group, there has been a significant increase in different relative organ weights compared to sham-operated control, while the uterine weight was found to be decreased. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 22 publications
(24 reference statements)
5
18
0
1
Order By: Relevance
“…These results revealed a low level of toxicity of 13cRA on bone and liver cells. These results are in agreement with fi ndings reported by other authors [Fahmy & Soliman, 2009;Mukherjee et al, 2004;Wei et al, 2007], who demonstrated that bone remodeling in rats is accelerated after ovariectomy-induced model of osteoporosis. These results are consistent with the data from Hotchkiss et al [2006] who showed that retinoids in large doses cause an increase of periosteal resorption in relation to periosteal extension or disposal of minerals, which ultimately leads to the reduction in the diameter of bone mineral loss.…”
Section: Oxidative and Antioxidative Activity In Liver Kidney And Ovarysupporting
confidence: 93%
“…These results revealed a low level of toxicity of 13cRA on bone and liver cells. These results are in agreement with fi ndings reported by other authors [Fahmy & Soliman, 2009;Mukherjee et al, 2004;Wei et al, 2007], who demonstrated that bone remodeling in rats is accelerated after ovariectomy-induced model of osteoporosis. These results are consistent with the data from Hotchkiss et al [2006] who showed that retinoids in large doses cause an increase of periosteal resorption in relation to periosteal extension or disposal of minerals, which ultimately leads to the reduction in the diameter of bone mineral loss.…”
Section: Oxidative and Antioxidative Activity In Liver Kidney And Ovarysupporting
confidence: 93%
“…It is considered as a dietary source of lignans, a type of phytoestrogen (Hernandez et al, 2004). Our previous study in an ovariectomized rat model of osteoporosis clearly established the importance of an oil extract of garlic as a possible nutraceutical which has therapeutic potential in preventing ovarian hormone insufficiencyinduced osteoporotic changes by influencing primary and secondary osteoporotic marker parameters and also bone density (Mukherjee et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that onion, garlic and parsley can inhibit bone resorption in ovariectomized rats (22,23). Quercetin from onion extract inhibits the differentiation of osteoclast progenitor into pre-osteoclasts and actin ring formation (24).…”
Section: Discussionmentioning
confidence: 99%